2006
DOI: 10.1027/1618-3169.53.3.233
|View full text |Cite
|
Sign up to set email alerts
|

The Mere Exposure Effect Is Sensitive to Color Information

Abstract: Priming effects in perceptual tests of implicit memory are assumed to be perceptually specific. Surprisingly, changing object colors from study to test did not diminish priming in most previous studies. However, these studies used implicit tests that are based on object identification, which mainly depends on the analysis of the object shape and therefore operates color-independently. The present study shows that color effects can be found in perceptual implicit tests when the test task requires the processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Accordingly, other investigators proposing that the mere exposure effect can be explained by processing fluency, rather than affect, have used procedures that overlap encoding and retrieval performance demands (e.g., requiring liking ratings at both study and test) or instructions that connect study to test (e.g., describing the experiment as a memory test which implies stimulus repetition). This methodology encourages awareness of the relationship between study and test stimuli and the results generated from it may be most informative when describing conscious preference formation ( Hupbach et al, 2006 , Experiments 1 and 2; Lawson, 2004 , Experiment 1; Topolinski and Strack, 2009 , Experiments 1–3).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, other investigators proposing that the mere exposure effect can be explained by processing fluency, rather than affect, have used procedures that overlap encoding and retrieval performance demands (e.g., requiring liking ratings at both study and test) or instructions that connect study to test (e.g., describing the experiment as a memory test which implies stimulus repetition). This methodology encourages awareness of the relationship between study and test stimuli and the results generated from it may be most informative when describing conscious preference formation ( Hupbach et al, 2006 , Experiments 1 and 2; Lawson, 2004 , Experiment 1; Topolinski and Strack, 2009 , Experiments 1–3).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these studies, the preference for the repeated stimulus should have increased rather than decreased. This inconsistency cannot be explained based on stimulus types, since studies have shown the mere exposure effect to exist across among a wide range of stimulus types, such as words (Zajonc, 1968; Monahan et al, 2000; Topolinski and Strack, 2009; Garcia-Marques et al, 2010), photographs (Bornstein and D'Agostino, 1992; Crisp et al, 2009), polygons (Bornstein and D'Agostino, 1992), random-dot patterns (de Vries et al, 2010), line drawings (Hupbach et al, 2006), and most relevantly, colorful paintings (Zajonc et al, 1972) which are similar to the natural scene pictures used in Park et al (2010). …”
Section: Introductionmentioning
confidence: 99%